2000
DOI: 10.2307/2656880
|View full text |Cite
|
Sign up to set email alerts
|

ABA prevents the second cytokinin‐mediated event during the induction of shoot buds in the moss Funaria hygrometrica

Abstract: The induction of shoot buds in the moss Funaria hygrometrica is a classic and quantitative bioassay for cytokinin. This cytokinin-stimulated response can be inhibited by the plant hormone abscisic acid, ABA; the inhibition is concentration dependent and was proposed for use as a bioassay for ABA. This paper characterizes the ABA inhibition of the cytokinin-stimulated formation of shoot buds. Experiments transferring protonema between cytokinin and cytokinin plus ABA show that ABA does not interfere with the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(18 citation statements)
references
References 28 publications
(64 reference statements)
1
16
0
Order By: Relevance
“…Abscisic acid treatment inhibits the precocious germination of somatic embryos and reduces secondary embryo formation (Choi and Jeong 2002;García-Martín et al 2005). In the moss Funaria hygrometrica, adventitious shoot formation is inhibited by ABA (Christianson 2000). Temporary pretreatment of ABA stimulated adventitious shoot proliferation in sesame.…”
Section: Resultsmentioning
confidence: 99%
“…Abscisic acid treatment inhibits the precocious germination of somatic embryos and reduces secondary embryo formation (Choi and Jeong 2002;García-Martín et al 2005). In the moss Funaria hygrometrica, adventitious shoot formation is inhibited by ABA (Christianson 2000). Temporary pretreatment of ABA stimulated adventitious shoot proliferation in sesame.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that bud formation for the gametophore of Funaria hygrometrica (Valadon and Mummery 1971) and Timmiella anomala (Chopra and Kapur 1989) is inhibited by ABA. This is probably due to the effect of ABA in counteraction with the bud-promoting action of cytokinin (Christianson 2000). Furthermore, ABA inhibited formation of gametangia in the moss Bryum argenteum and Microdus brasiliensis at high concentrations (Bhatla and Chopra 1981;Chopra and Mehta 1987).…”
Section: Bryophytes and Abamentioning
confidence: 99%
“…The induction of shoot buds in the moss Funaria hygrometrica is a classic quantitative bioassay for cytokinins. Later Christianson (2000) localized the inhibitory action of ABA to a particular time in the process of bud formation. Experiments transferring protonema between cytokinin and cytokinin plus ABA show that ABA does not interfere with the initial perception of cytokinin.…”
Section: Introductionmentioning
confidence: 99%